Sistem Alat Ukur Detak Jantung Dan Nafas Manusia Menggunakan Arduino Uno - Andreas Nggaba Ngabi; Ali Warsito; Jonshon Tarigan (Universitas PGRI Semarang, 2022)
This research was conducted by identifying one of the problems that exist in the world of health, namely monitoring human health conditions in real time and automatically. The purpose of this study is to realize an Arduino Uno-based instrumentation tool by utilizing a heart rate sensor and respiratory frequency in humans in overcoming these problems. The research method applied is to measure health conditions by determining two indicators of the measured object of research, namely heart rate and breathing frequency. As comparison data, measuring instruments are used in determining the accuracy of the instrumentation made. Based on the measurement results from nine samples of health condition data, the results for the heart rate were 3.33 BPM with an accuracy of 96.67%, and the results for the respiratory frequency were 2.4 X/min with an instrument accuracy of 97.60%. With these results, it is concluded that the instrumentation made is accurate enough to be used as an additional means of monitoring health conditions in real time and automatically..Keywords: Arduino Uno, Heart rate, breathing frequency